Bilateral Trade and Similarity of Income Distributions: The Role of Second Moments - Peter S. Eppinger; Gabriel J. Felbermayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
We use an augmented gravity model to revisit the effect of similarity in income distributionson bilateral trade flows. Disentangling supply-side and demand-side mechanisms,we document a robust new regularity: while differences in average incomes betweentwo countries increase trade, differences in income dispersion reduce it. Our result shedsnew light on the Linder hypothesis and strengthens the role of non-homothetic preferencesin trade theory.
Keywords: F10; D31; 330; International trade; income distribution; gravity model; Linder hypothesis; nonhomothetic preferences